Pre-Pregnancy Obesity Phenotypes and the Risk of Oligohydramnios: A Large Population-Based Cohort - Kyung Eun Lee; Ye Bin Park; In Yang Park; Jae Eun Shin; Kyung Do Han (Journal of Clinical Medicine, 2026)
Background/Objective: Maternal obesity is an established risk factor for adverse obstetric outcomes. However, its association with oligohydramnios remains unclear and has been examined using body mass index (BMI) alone. We assessed pre-pregnancy general and abdominal obesity in relation to oligohydramnios. Methods: We analyzed 762,104 women who delivered between 2010 and 2018 and had undergone a national health examination within two years before conception. Women were classified into four phenotypes by BMI (general obesity: ≥25 kg/m2) and waist circumference (abdominal obesity: ≥85 cm). Odds ratios were estimated by logistic regression adjusted for pre-pregnancy characteristics, and interaction was tested on the additive and multiplicative scales. Results: Oligohydramnios occurred in 13,860 women (1.82%). Relative to women with neither phenotype, adjusted odds were increased for abdominal obesity alone (1.163; 95% CI 1.013–1.336), general obesity alone (1.125; 95% CI 1.051–1.204), and both (1.336; 95% CI 1.241–1.438). Absolute risk was 2.19% among women with both phenotypes and 1.79% among those with neither, with no interaction on either scale (p = 0.811). Conclusions: General and abdominal obesity were each associated with oligohydramnios. Because nearly one in four women with abdominal obesity had a BMI below the obesity threshold, assessment by BMI alone leaves part of this risk unrecognized.